The Role of Quality Work of Life on Turnover Intention in Gading Pluit Hospital - Kartika Lilisantosa; Rokiah Kusumapradja; Rina Anindita; Endang Ruswanti (Budapest International Research and Critics University, 2021)
Turnover is a problem, often faced by an organization, including hospital organizations. High nurse turnover will disrupt hospital productivity, and increase hospital budgets to carry out recruitment, selection and training. Nurses might have the desire to move (Turnover Intention) which results in the nurse's decision to leave her job. Nurse turnover at Gading Pluit Hospital showed an increase from 9.3% (in 2019) to 15.5.0% (in 2020) with the largest percentage coming from inpatient nurses (86.7%). This study was conducted to identify the effect of Quality Work of Life (QWL), work stress, and organizational citizenship behavior (OCB) of inpatient nurses on turnover intention (TOI) at Gading Pluit Hospital. This research used mixed methods. Proof of the hypothesis using the causality method with SEM-PLS analysis then followed by qualitative method. The study was carried out from May to August 2021 using a saturated sample of 101 out of 107 nurses, followed by random inter-views with 5 nurses. The results showed that there was an influence of Quality of Work Life and Organizational Citizenship Behavior on Turnover Intention. OCB increased the effect of QWL in lowering TOI. Work stress with medium index has not affected OCB and TOI. Efforts to reduce Turnover Intention can be done by improving the Quality of Work Life and regulating the OCB behavior to in-crease a positive impact on nurses in carrying out their duties and functions. Interview results indicate the need to adjust the remuneration system, health insurance, and improve communication between management and nurses.